Metastatic Prostate Cancer to the Urethra Masquerading as Urothelial Carcinoma - Zardawi, Ibrahim (Urol Case Rep, 2016)
Tumors of the urethra, whether primary or metastatic, are very rare. The true nature of urethral neoplasm is not always obvious clinically nor in routine histological sections. Immunostains should be performed on such lesions because of management implications. We present a case of multiple metastases to the urethra from a prostatic carcinoma, masquerading as multiple urothelial carcinomas. Pathologists and urologists should be aware of the possibility of metastasis from the prostate.